The economic consequences of single motherhood on children’s cognitive outcomes in Indonesia - Nugroho, Wisnu Setiadi; Afifah, Evi Noor; Perdana, Andika Ridha Ayu; Syarifah, Zahra Amaila (Economic Journal of Emerging Markets, 2026)
Purpose — Single motherhood is widely associated with poorer child outcomes, yet it remains unclear whether these disadvantages stem from family structure itself or from the economic shocks that accompany it. This distinction is particularly important in developing-country contexts, where weak social protection and labor market informality may amplify both channels. We examine how different pathways into single motherhood affect children’s cognitive development.Methods — We use longitudinal data from the Indonesia Family Life Survey (IFLS) and employ Structural Equation Modeling (SEM) to estimate both direct and indirect effects of maternal marital status on children’s cognitive outcomes, while controlling for demographic and household characteristics.Findings — The results show that children in single-mother households, particularly those experiencing divorce, have lower cognitive scores. Poverty plays a key mediating role, as higher poverty levels are associated with worse cognitive outcomes. Households headed by divorced individuals exhibit higher poverty, while the effect of widowhood is smaller and not statistically significant. In addition, larger household size and greater distance from economic centers increase poverty, whereas higher education of the household head and per capita expenditure reduce it.Implication — The findings suggest that policies targeting single-mother households should address both economic vulnerability and structural constraints, including limited access to services and unequal labor market opportunities.Originality — This paper contributes to the limited longitudinal literature in developing countries by comparing divorce and widowhood and their roles in perpetuating intergenerational disadvantages through economic and non-economic channels.